2022
DOI: 10.1002/ajpa.24495
|View full text |Cite
|
Sign up to set email alerts
|

The genomic formation of Tanka people, an isolated “gypsies in water” in the coastal region of Southeast China

Abstract: Objectives: Three different hypotheses proposed via the controversial evidence from cultural, anthropological, and uniparental genetic analyses, respectively, stated that Tanka people probably originated from Han Chinese, ancient Baiyue tribe, or the admixture of them. Therefore, the genetic origin and admixture history of the Tanka people, an isolated "Gypsies in water" in the coastal region of Southeast China, are needed to be genetically clarified using genome-wide SNP data. Materials and methods: To elucid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, the genetic origin and phylogenetic relationships within TK-speaking populations remain to be further characterized [ 34 , [46] , [47] , [48] ]. We collected and genotyped 24 BBN individuals and merged newly generated data with previously published data to produce three datasets—a low-density merged HO dataset [ 28 , 29 ], a middle-density merged 1240K dataset, and a high-density merged WGS dataset [ [49] , [50] , [51] , [52] , [53] , [54] , [55] ] to provide new insights into the demographic history, population structure, and human genetic diversity of TK-speaking individuals. The ADMIXTURE result based on a high-density dataset identified a unique genetic component that was greatest in TK-speaking Bouyei, indicating that the Bouyei populations possessed a unique genetic structure ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the genetic origin and phylogenetic relationships within TK-speaking populations remain to be further characterized [ 34 , [46] , [47] , [48] ]. We collected and genotyped 24 BBN individuals and merged newly generated data with previously published data to produce three datasets—a low-density merged HO dataset [ 28 , 29 ], a middle-density merged 1240K dataset, and a high-density merged WGS dataset [ [49] , [50] , [51] , [52] , [53] , [54] , [55] ] to provide new insights into the demographic history, population structure, and human genetic diversity of TK-speaking individuals. The ADMIXTURE result based on a high-density dataset identified a unique genetic component that was greatest in TK-speaking Bouyei, indicating that the Bouyei populations possessed a unique genetic structure ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to explore the genetic relationship between TK people and other modern and ancient eastern Eurasians, we merged our genome-wide data with previously published modern and ancient people from the Allen Ancient DNA Resource (AADR), which formed a low-density merged HO dataset [ 28 , 29 ], including 56,814 SNPs, and a middle-density merged 1240K dataset, including 146,802 SNPs. To explore the fine-scale genetic structure and obtain phased genomes to illuminate the biological adaptation mechanisms, we combined our data with previously published Illumina data [ [49] , [50] , [51] , [52] , [53] , [54] , [55] , 62 ], 54 worldwide populations included in the HGDP [ 28 ], and 20 populations from Taiwan Island, SEA Island, and Oceania included in the Oceanian genomic resources [ 29 ], which formed the high-density merged WGS dataset and included 460,678 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…We retained 516,448 SNPs among 58 individuals in the following population genetic studies. We merged our data with previously published high-density SNP data that were genotyped via the Illumina array used in this study (Lu et al, 2020;Guo et al, 2021;Yao et al, 2021;Wang et al, 2021b;Zhang et al, 2021b;Chen et al, 2022;He et al, 2022;Wang et al, 2022;He et al, 2023c), previously reported Human Genome Diversity Project (HGDP) and Oceania genomic resource (Bergstrom et al, 2020;Choin et al, 2021), and Human Origins (HO) and 1240K datasets retrieved from the Allen Ancient DNA Resource (Jeong et al, 2019;Liu et al, 2020;Ning et al, 2020;Yang et al, 2020;Kutanan et al, 2021;Mallick et al, 2023) to form three different population genetic analysis datasets: high-density Illumina dataset (~461K overlapping SNPs), medium-density merged 1240K dataset (~147K), and low-density merged HO dataset (~57K).…”
Section: Sample Collection Array Genotyping and Reference Datasetmentioning
confidence: 99%
“…Therefore, the genetic origin and phylogenetic relationship within TK-speaking populations remained to be further characterized (32,(40)(41)(42). We collected and genotyped 24 Bouyei individuals from Guizhou Bannong and merged newly-generated data with previously published data to produce three datasets: low-density merged HO dataset (26,27); middle-density merged 1240K dataset, and high-density merged WGS dataset (43)(44)(45)(46)(47)(48)(49) to provide new insights into the demographic history, population structure and human genetic diversity of TK-speaking. The ADMIXTURE result based on a high-density dataset identified a unique genetic component maximised in TK-speaking Bouyei, indicating that Bouyei populations possessed a unique genetic structure (Figure 1A).…”
Section: Demographic History and Population Structure Within Tk-speak...mentioning
confidence: 99%